Identification and validation of a novel signature based on cell-cell communication in head and neck squamous cell carcinoma by integrated analysis of single-cell transcriptome and bulk RNA-sequencing - Wang, Jian; Sun, Hong-Cun; Cao, Cheng; Hu, Jian-Dao; Qian, Jing; Jiang, Tao; Jiang, Wen-Bo; Zhou, Shao; Qiu, Xiao-Wen; Wang, Hong-Li (Frontiers in Oncology, 2023)
The heterogeneous crosstalk between tumor cells and other cells in their microenvironment means a notable difference in clinical outcomes of head and neck squamous cell carcinoma (HNSCC). CD8+ T cells and macrophages are effector factors of the immune system, which have direct killing and phagocytosis effects on tumor cells. How the evolution of their role in the tumor microenvironment influences patients clinically remains a mystery. Using publicly available single-cell transcriptome data and bulk rna-sequencing, widely heterogeneous ligand-receptor interactions between tumor cells and other cells were identified. By constructing molecular subtypes of tumor-associated ligand-receptor genes, the differences of CD8+ T state and other immune cells in inflammatory infiltration, immunotherapy and clinical characteristics of those two molecular subtypes were investigated. With CD8+T cells from naive to exhaustion state, significantly decreased expression of protective factor (CD6 gene) is associated with poorer prognosis in patients with HNSCC. The role of macrophages in the tumor microenvironment has been identified as tumor-associated macrophage (TAM), which can promote tumor proliferation and help tumor cells provide more nutrients and channels to facilitate tumor cell invasion and metastasis. In addition, based on the strength of all cell-cell communication (ccc) in the tumor microenvironment, we identified five prognostic ccc gene signatures (cccgs), which were identified as independent prognostic factors by univariate and multivariate analysis. The predictive power of cccgs was well demonstrated in different clinical groups in train and test cohorts. Overall, our study highlights the propensity for crosstalk between tumors and other cells and developed a novel signature on the basis of a strong association gene for cell communication that has a powerful ability to predict prognosis and immunotherapy response in patients with HNSCC. This may provide some guidance for developing diagnostic biomarkers for risk stratification and therapeutic targets for new therapeutic strategies.